Pengaruh Sistem Informasi Akuntansi terhadap Pengendalian Internal Persediaan (Pendekatan Kuantitatif pada Kedai Kopi Talkie Space di Kabupaten Garut) - Siska Marlina; Dida Farida; Marissa Disthy Putri; Berliana Putri (SENTRI: Jurnal Riset Ilmiah, 2025)
Effective inventory management is a crucial component in supporting operational efficiency and the reliability of financial reporting, particularly in Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector, which are characterized by high inventory turnover. Weaknesses in inventory recording and monitoring can lead to stock discrepancies, cost inefficiencies, and decreased business performance. This study aims to analyze the effect of accounting information systems (AIS) on the effectiveness of internal inventory control at Talkie Space Coffee Shop in Garut Regency. The research employs a quantitative approach using a survey method, with data collected through the distribution of Likert-scale questionnaires to 30 respondents directly involved in inventory management. The data were analyzed using validity, reliability, and normality tests, as well as simple linear regression with the assistance of SPSS software. The results indicate that the accounting information system has a positive and significant effect on the effectiveness of internal inventory control, with a regression coefficient of 0.678, a t-value of 4.52, and a significance value of 0.000. These findings suggest that the implementation of a well-structured AIS can improve the accuracy of inventory records, strengthen monitoring processes, and minimize the risk of errors and stock discrepancies. Practically, this study emphasizes the importance for MSMEs to develop and optimize accounting information systems supported by adequate technology and enhanced human resource competencies through continuous training in order to improve the effectiveness of internal inventory control and overall operational performance.